Cyber Risk Insurance: Evaluating Insurers’ Preparedness in an Increasingly Digital World - Morsi, Sami A. (Journal of Cultural Analysis and Social Change, 2025)
The accelerating pace of digital transformation has heightened organizations’ exposure to cyber threats, positioning cyber risk insurance as a vital mechanism for financial protection and resilience. This study examines insurers’ preparedness to address the rising frequency, sophistication, and unpredictability of cyberattacks in an increasingly digital world. The research evaluates key aspects of preparedness, including underwriting practices, data analytics capabilities, risk modeling approaches, claims management structures, and collaboration with cybersecurity service providers. Using a combination of literature review, industry reports, and qualitative insights from insurance professionals, the study explores persistent challenges such as limited historical loss data, rapidly evolving attack vectors, regulatory uncertainties, and the difficulty of accurately quantifying intangible cyber risks. The findings reveal significant gaps between existing insurance models and the dynamic nature of cyber threats, emphasizing the need for more adaptive risk assessment tools, enhanced information-sharing frameworks, and greater investment in predictive technologies such as AI-driven threat intelligence. Additionally, the study highlights the importance of developing standardized policy wording to address coverage ambiguity and improve customer trust. Overall, the research underscores that while insurers have made considerable progress, further advancements in technology integration, strategic partnerships, and regulatory alignment are essential to strengthening the effectiveness and sustainability of cyber risk insurance.